The Commentary as Polemical Tool: The Anonymous Commentator on the Theaetetus against the Stoics - Bonazzi, Mauro (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2008)
AbstractContrary to what is usually assumed, the Anonymous Commentator on the Theaetetus is philosophically stimulating, as the confrontation with Stoicism shows. The Anonymous Commentator displays a subtle strategy, aiming not so much to reject distinctively Stoic doctrines as to incorporate them into his own Platonist system, on the assumption that only the latter can secure adequate foundations to the doctrines. The Anonymous Commentator can thus appropriate Stoicism and definitely settle the ancient quarrel between Stoicism and Platonism. Besides, Stoicism is not a separate issue, but is part of a wider issue. For the comparison with Stoicism also helps the Anonymous Commentator to defend his unitary interpretation of the Platonic-Academic tradition. Commenting a text is not a neutral practice but one of the most important aspects of post-Hellenistic philosophy.